Model Pembelajaran Quantum Learning dan Quantum Teaching Berbasis Pendidikan Karakter Terhadap Motivasi Belajar Peserta Didik Kelas I Madrasah Ibtida'iyyah Lebo Sidoarjo - Awaludin Jamil (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to test the effectiveness of the Quantum Learning and Teaching model based on character education on the learning motivation of first-grade students at MI Lebo Sidoarjo. This study used a quasi-experimental nonequivalent control group design with pre-test and post-test questionnaire instruments. Data analysis used the Independent Samples t-test and Normalized Gain (N-gain). The results showed that the experimental group implementing the Quantum model experienced a significant increase in learning motivation (p=0.000) compared to the control group. The N-gain score of the experimental group (0.68) was in the medium category, far exceeding the control group (0.25) in the low category.